BIOMETRIC ANALYSIS OF DIVERSITY IN PACIFIC OCEAN COCONUT POPULATIONS - M.J. Ratnambal; V. Arunachalam; Augustin Jerard B.; Sarankumar Rizwal; V.Damodaran (International Coconut Community, 2002)
Coconut (Cocos nucifera L.) is an important perennial multi-purpose palm commonly grown in humid tropics. The crop belongs to the monotypic genus Cocos having 2n=2x=32 chromosomes. The crop supports millions of resource poor farm families in islands and coastal ecosystems. Genetic improvement of coconut palm is in progress in many research stations for improving yield and tolerance to biotic and abiotic stress. Knowledge of genetic divergence of the crop is helpful in improvement of the crop. Pacific islands are supposed to contain wild forms and rich diversity of coconut. Genetic divergence studies were carried out using morphological, fruit component characters by many workers. Sugimura et al., (1997) analysed the diversity of 39 accessions of coconut as three major groups typica, nana and javanica using agronomic and botanical traits. Nana was found to be an aggregate group, which was far distant from typica. But, javanica was found to be an intermediate type.